Indium Oxide Nanotubes Obtained by Radical Beam Epitaxy - V.V. Kidalov; А.F. Dyadenchuk (Журнал нано- та електронної фізики)
We propose an original method for producing indium oxide nanotubes embedded in a porous InP surface. Annealing of porous InP samples obtained by electrochemical etching is performed in a flux of atomic oxygen. After annealing the inner surface of the walls of each pore was covered with oxygen throughout its length from the base (indium phosphide column) to the sample surface forming oxygen-containing nanotubes which mimic the shape of pores. Chemical composition of the surface of the obtained samples was studied using the method of energy dispersive X-ray analysis (EDAX). Structure of the obtained samples was also studied by the X-ray diffraction method.